Sustained outbreak of blaVIM-1 harbouring pathogens in an Italian tertiary hospital: Genomic insights into persistence and spreading - Saluzzo, Francesca; Di Marco, Federico; Batignani, Virginia; Moghaddasi, Kiarash; Averara, Franca; Bracco, Silvia; Del Castillo, Gabriele; Farina, Claudio; Cirillo, Daniela Maria (Journal of Global Antimicrobial Resistance, 2025)
•Genomic analysis reveals a prolonged outbreak of blaVIM-1 producing bacteria.•Hospital environment serves as a hidden reservoir for blaVIM-1 persistence.•A shared class 1 integron facilitates blaVIM-1 spread across multiple species.•Whole-genome sequencing reveals complex transmission dynamics in the outbreak. We investigated an outbreak of blaVIM harbouring pathogens lasting over a year, affecting patients in an intensive care unit (ICU) in a tertiary hospital in Bergamo, Italy. To identify transmission routes of pathogens, we combined classical epidemiological investigation with the molecular identification of the mobile genetic elements (MGEs), integrons, and resistance cassettes that could have played a role in the outbreak persistence. Short and long reads sequencing were performed. Transmission, resistome, and virulome analysis were conducted, as well as the identification of plasmids and integrons harbouring blaVIM-1. Forty-four blaVIM harbouring isolates, including Enterobacterales and Pseudomonadaceae, were identified from patients and environmental samples. The strains exhibited diverse resistomes and virulomes, with high mortality rates among infected patients. The performed assembly analysis did not support the hypothesis of interspecies plasmid transmission, but, nonetheless, genomic analysis revealed a consistent presence of a class 1 integron (IntI1) in all the analysed strains. The identification of the same IntI1 in clinical and environmental samples suggests a potential reservoir for resistant strains in the hospital environment. These findings emphasize the need for comprehensive infection control measures, including genomic-based surveillance, to address MGEs’ horizontal spreading and persistence in the healthcare setting. © 2025 The Author(s). Published by Elsevier Ltd on behalf of International Society for Antimicrobial Chemotherapy.